A Comprehensive Review of Orthognathic Surgery: Fixation, Relapse, and Complications. Issue 2 (June 2022) - Puthumana, Joseph S.; Lopez, Christopher D.; Magrath, Walker J.; Lake, Isabel V.; Girard, Alisa O.; Redett, Richard J.; Steinbacher, Derek M.; Grant, Michael P.; Lopez, Joseph; Yang, Robin
Background: This study aims to investigate all papers on orthognathic fixation to better understand changes in operative techniques and fixation materials and to better compare relapse and complication rates. Methods: A PubMed search was conducted of "orthognathic" AND "fixation" in the title or abstract between 1989 and 2020. Results: Three reviewers independently screened 439 papers and extracted data from 166 included papers. Of these studies, 118 investigated sagittal split ramus osteotomies (SSRO), 96 LeFort osteotomies, 25 genioplasties, and 21 intraoral vertical ramus osteotomies (IVRO). The most used fixation materials in the maxilla were titanium miniplates with monocortical screws (n = 65), followed by resorbable miniplates (n = 10); in the mandible, the most common were titanium miniplates (n = 67) and titanium bicortical screws (n = 49). Wide variability was demonstrated in relapse rates by operation, fixation type, and relapse time-point studied. Meta-analysis revealed a significantly higher infection rate in SSRO versus LeFort ( P = .003) and, surprisingly, a trend toward higher relapse rate in titanium versus resorbable fixation at 6 months in SSRO setback ( P = .08). Conclusion: This study reports all the available data on relapse rates across techniques, with non-inferiority of bicortical screws versus miniplates.